2018
DOI: 10.1073/pnas.1800869115
|View full text |Cite
|
Sign up to set email alerts
|

Shewanella oneidensisas a living electrode for controlled radical polymerization

Abstract: Metabolic engineering has facilitated the production of pharmaceuticals, fuels, and soft materials but is generally limited to optimizing well-defined metabolic pathways. We hypothesized that the reaction space available to metabolic engineering could be expanded by coupling extracellular electron transfer to the performance of an exogenous redox-active metal catalyst. Here we demonstrate that the electroactive bacterium can control the activity of a copper catalyst in atom-transfer radical polymerization (ATR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(108 citation statements)
references
References 61 publications
(75 reference statements)
8
100
0
Order By: Relevance
“…231,236,279 Furthermore, the intracellular metabolism can be coupled with extracellular redox transformations to manufacture functional materials such as polymers and inorganic particles. [280][281][282] These materials may provide additional benefits to promote extracellular electron transfer or cytoprotection. 281 Advanced photochemistry provides another thrust in future development.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…231,236,279 Furthermore, the intracellular metabolism can be coupled with extracellular redox transformations to manufacture functional materials such as polymers and inorganic particles. [280][281][282] These materials may provide additional benefits to promote extracellular electron transfer or cytoprotection. 281 Advanced photochemistry provides another thrust in future development.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…S. oneidensis has evolved to use inorganic materials as an electron acceptor during anaerobic respiration. . S. oneidensis can deliver electrons to inorganic acceptor materials both by electron shuttles and via direct surface‐to‐surface contact mediated by its Mtr respiratory pathway, which consists of multiple different proteins which pass electrons from the bacterial cytoplasm, through the cell membranes, and up to the surface of the bacterium.…”
Section: Introductionmentioning
confidence: 99%
“…[14,22,23] One intriguing possibility to reduce graphene oxide in a more sustainable, easily up-scalable, and cost-efficient way is via the metal-oxide-reducing bacterium Shewanella oneidensis. [24][25][26] S. oneidensis has evolved to use inorganic materials as an electron acceptor during anaerobic respiration.. [27] S. oneidensis can deliver electrons to inorganic acceptor materials both by electron shuttles and via direct surface-to-surface contact mediated by its Mtr respiratory pathway, which consists of multiple different proteins which pass electrons from the bacterial cytoplasm, through the cell membranes, and up to the surface of the bacterium. [25,[26] When graphene oxide is provided, the electrons from S. oneidensis react with the oxygen groups of the graphene oxide, leading to a restoration of the sp 2 orbitals forming the characteristic hexagonal lattice of graphene.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, in the field of polymer chemistry, it has been recently reported that radical polymerization can be performed by utilizing microbial EET. [ 73–75 ] For example, Magennis et al. utilized Escherichia coli ( E. coli ) and Pseudomonas aeruginosa to regenerate Cu(I), a catalyst for the polymerization, to synthesize microbe‐templated polymers.…”
Section: General Features Of Type I Mediatorsmentioning
confidence: 99%